FAKTOR PENDORONG NIAT BERKUNJUNG ULANG WISATAWAN MEDIS INDONESIA KE MALAYSIA - Adelyn Adelyn; Renza Fahlevi; Fitriana Aidnilla Sinambela (LPPM STIE Muhammadiah Bandung, 2026)
The research uses a quantitative approach to examine the relationship between safety and security, price reasonableness, and word-of-mouth communication on the image of a medical tourism destination and the revisit intention of Indonesian medical tourists to Malaysia. The study sample included Indonesian who had previously traveled to Malaysia for medical treatment. The sampling technique used was purposive sampling with 210 respondents. The collected data were processed using the Partial Least Squares Structural Equation Modeling (PLS-SEM) approach. The results show that two variables safety and security and price reasonableness are important in shaping Malaysia's positive image as a medical tourism destination, but word-of-mouth communication is not. Furthermore, a positive destination image is an important variable in increasing tourists' intention to return to Malaysia for medical treatment.